Lansoprazole-Based Colorimetric Chemosensor for Efficient Binding and Sensing of Carbonate Ion: Spectroscopy and DFT Studies - Darroudi, Mahdieh; Mohammadi Ziarani, Ghodsi; Bahar, Shahriyar; Ghasemi, Jahan B.; Badiei, Alireza (Frontiers in Chemistry, 2021)
The new benzimidazole based receptor Lansoprazole has been used to detect carbonate anion by naked-eye and Uv-Vis spectroscopy. This receptor revealed visual changes with CO32- anion in ethanol. No detectable color changes were observed upon the addition of any other tested anions. The lansoprazole chemosensor selectively recognizes CO32- ion over the other interference anions in the ethanol, followed by deprotonation and reflected 1:1 complex formation between the receptor and the carbonate ion. Lansoprazole exhibits splendid selectivity toward carbonate ion via a visible color change from colorless to yellow with a detection limit of 57 μM. The binding mode of CO32- to receptor L is supported by Density Functional Theory calculation. Moreover, this receptor shows a practical visible colorimetric test strip for the detection of carbonate ions. The transition states calculation demonstrates the occurrence of reaction from L to L-CO32- after overcoming an energy barrier of 10.1 kcal/mol, and there is considerable interaction energy between L and CO32- (94.9 kJ/mol), both of which confirmed that receptor L has high sensitivity and selectivity to the carbonate ion. The theoretical studies were performed to acquire an electronic description of the complexation mechanism by CO32- as well as to study bonding and structure in the complex. The optimized structures and binding mechanisms were supported with a high correlation and agreement by spectroscopy and DFT calculations.